Kriteria Pemilihan Karier antara Orang Tua dan Anak pada Masa Emerging Adulthood - Dian Erlina; Srisiuni Sugoto; Listyo Yuwanto (Fakultas Psikologi Universitas Pancasila, 2014)
Career selection is something that every individual will experience, especially those who is in emerging adulthood stage. One factor that can make the career selection uneasy is family. This is usually caused by the desire of parents to play a role in the selection of their child's career. If parents and children have a common in terms of career, then there will be no problems occur. Problems often occur when parents impose on children's career choice. This study aimed to describe the selection criteria for a career on the subject of emerging adulthood and the elderly. Subjects in this study were the pairs of father, mother, and their children aged 18-25 years that selected by purposive sampling method (N=100). Data were taken using a questionnaire. The data will be analyzed by the cluster method, frequency distributions, and cross-tabulations. The results showed 3 groups on the subjects father, mother, and child. In the entire group formed, there are criteria that are considered very important by each group. Groups of parents are very concerned with the financial criteria and professional contribution to the work, while the groups of child consider that the values and personal expectations are the very important criteria in choosing a career. There are only 10 pairs (10%) of parents and children who have common criteria in choosing a career. The results of the study are discussed further.